Hexachlorobenzene induces TGF-β1 expression, which is a regulator of p27 and cyclin D1 modifications - Chiappini, Florencia Ana (2014)
Hexachlorobenzene (HCB) is an organochlorine pesticide widely distributed in the environment. In this study we have demonstrated that HCB induced loss of cell viability and alterations in cell cycle regulation in FRTL-5 rat thyroid cells. Analysis of cell cycle distribution by flow cytometric analysis demonstrated that HCB induced cell cycle arrest at G2/M and at G0/G1 phase, inhibiting cell cycle progression at the G1/S phase, after 24 h and 72 h of treatment. HCB-treatment resulted in an increase in transforming growth factor-beta (TGF-β1) mRNA levels, a negative regulator of cell growth in thyroid epithelial cells. Time-dependent studies showed that both cytosolic and nuclear p27 protein levels were increased by 5 μM HCB. After 24 h of treatment, total p27 in whole cells lysate was increased. Dose-dependent studies, demonstrated that HCB (0.005, 0.05, 0.5 and 5 μM) increased p27, both in the cytosol and nucleus. HCB (5 μM) induced a concomitant decrease in nuclear cyclin D1 protein levels, in a time-dependent manner. We have also demonstrated that TGF-β1 Smad signaling is involved in HCB-induced alterations of p27 and cyclin D1 protein levels. On the other hand, ERK1/2 activation is not involved in the alteration of cell cycle regulatory proteins.